Students’ Vocabulary Mastery By Using Animation Video on English Language Teaching - Munawir, Ahmad; Inayah, Nur; Firmansyah, Nur Putriani; Huda, Nabila (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The purpose of the study was to determine whether or not the second-year students at MTs As'adiyah Putri 1 Sengkang benefit from using animation videos to expand their vocabulary. The pre-experimental approach was used by the researcher, who used a one-group pre-test and post-test design. The second year of MTs As'adiyah Putri 1 Sengkang in the academic year 2020–2021 made up the study's population. The information was gathered via a vocabulary exam (pre-test and post-test). Cluster random sampling was employed as the sampling method. The researcher conducted a t-test study to determine whether or not the usage of video as a teaching tool improved students' vocabulary. The examination of the data revealed a substantial difference between the pre-test and post-tests. It was demonstrated by the significance value of 0.000, which was lower than the level of significance (α) = 0.05. The average post-test score (84.50) exceeded the average pre-test score (52.90). Based on the study's data and analysis, the author came to the conclusion that employing video as a teaching tool improved the vocabulary of second-year MTs As'adiyah Putri 1 Sengkang.